STUDENTS’ PERCEPTION OF ONLINE ENGLISH LEARNING IN THE COVID-19 PANDEMIC AT SMA NEGERI 1 PERANAP (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research found the perception of students on online English learning during the Covid-19 pandemic. The researcher conducted sample testing in two classes, namely X IPA 3 and XII IPA 2, at SMA Negeri 1 Peranap. This research is descriptive research with a quantitative approach. The data was collected through a questionnaire using a Google Form shared in the WhatsApp group of each class. Out of 48 respondents were participating in this research. Based on the result data, the responses from students tended to be neutral towards online English learning during the covid-19 pandemic. Part of items related to the online English learning process with a percent of 42.1% disagrees, part of items related to the online English learning facilities with a percent of 39.1% agrees, part of items related to the online English learning motivation with a percent of 47.2% disagrees. Then part of the items related to the understanding of online English learning with a percent of 43.8% disagrees. The results of the data collected can conclude, namely, the neutral response that students have not adapted to online English learning.Key Words: Students, Perceptions, Online English Learning